The Complete Book of Parenting : Everything you Need to Know to Care for Your Child, from Before Birth to Adolescence. - Published by Ebury Press Ltd (London Ebury Press, 1996)
Whether you need to know which games will stimulate your toddler's memory skills, how to choose a car seat or what to do when your 10-year-old becomes vegetarian, this guide aims to help. From pregnancy to dealing with teenage anxieties, a team of expert contributors offers their advice.
Include Color Illustration and Index
Keywords: Parenting -- Child rearing -- Child development